Features of Vocational Education Management in the Region - Kamasheva, Yuliya L.; Goloshumova, Galina S.; Goloshumov, Aleksey Y.; Kashina, Svetlana G.; Pugacheva, Natalya B.; Bolshakova, Zemfira M.; Tulkibaeva, Nadezhda N.; Timirov, Fedor F. (International Review of Management and Marketing, 2016)
The relevance of the article is reasoned by the increasing role of vocational education in the regional economy. In modern conditions, vocational education is considered as a systemic integrity of integrative interaction of education, science and industry, aimed at experts' forming who is ready for the life - long learning, capable to a certain type of professional activities, self-organization and competitiveness on the labor market. The purpose of the article is to find out management features of vocational education in the region. The leading method is the method of action research (AR), allowing to obtain new knowledge about the management of vocational education in the region and to suggest methods for its optimization to improve the competitiveness of vocational education institutions in the international educational market and to obtain qualitatively new results in the process of vocational training. The article reveals the essence of management of vocational education in the region; clarifies trends in the management of vocational education in the region; identifies problems in the management of vocational education in the region, defines and justifies their solution methods (the implementation of modern financial and economic mechanisms of vocational education institutions' activities; development of normative-legal support of activities of vocational education institutions; the creation of new adaptive forms and mechanisms of management of vocational education in the region; making, implementation and development of quality management systems of vocational education). Article Submissions can be useful for research and teaching staff of vocational education system, for specialists of education management authorities and regional authorities. Keywords: management of vocational training, management methods of vocational education, economic and financial mechanisms, normative-legal support of professional educational institutions' activities, the management of quality of vocational education. JEL Classifications: I21, I23, Z13